PENERAPAN METODE DOUBLE EXPONENTIAL SMOOTHING DARI BROWN UNTUK PREDIKSI PENDAPATAN MINIMARKET - Lina Lina; Andi Nur Rahman; Isnurani Isnurani (LPPM Universitas Bina Bangsa, 2024)
Indomaret is a trade mini market that sells retail goods originating from factories and then distributed at retail prices. Indomaret's revenue is obtained from the sale of merchandise according to the price determined by the company. However, in the midst of the onslaught of Covid-19 and the threat of a recession, there is a problem from the sales side, namely Indomaret's revenue has decreased since November 2021 to October 2022. Another problem Indomaret is also facing is how to make the minimarket's income reach the target set by the company and adjust it to the stock of goods which is kept in store. So that efforts are needed to forecast sales results in the future and then determine a strategy that is in accordance with the results of the forecast. This study uses the Double Exponential Smoothing Brown Linear 1 parameter method which aims to predict revenue results in November and December 2022 and determine the best alpha parameter. Obtained the amount of inomaret Hj. Enting in November 2022 is IDR 388,772,979.030 and December 2022 is IDR 367,905,870.938. The parameter that minimizes the error value is alpha 0.4 with a MAPE value of 7.6%.